Primary idiopathic CNS non-amyloidogenic light chain deposition disease complicated by treatment-resistant focal seizure disorder. (January 2019) - Grainger, Brian T.; Issa, Samar; Anderson, Neil E.
Highlights: LCDD is disorder involving deposition of immunoglobulin light chains. CNS-restricted LCDD is among the rarest manifestations. This unique case is complicated focal onset epilepsy with for which therapy proved difficult. Abstract: Light chain deposition disease (LCDD) is a systemic disorder characterised by the pathologic deposition of immunoglobulin light chains, which is histologically distinguished from amyloidosis by failure to stain with Congo red. Central nervous system (CNS)-restricted LCDD is among the rarest manifestations. We describe a unique case complicated by focal onset epilepsy with impaired awareness for which control with anticonvulsant therapy proved difficult.